ACE I/D Genotype and Risk of Non-Contact Injury in Moroccan Elite Athletes: A Pilot Study - El Mokhtar El Ouali; Jihan Kartibou; Juan Del Coso; Rashmi Supriya; Ismail Laher; Zineb El Kettani; Hassan Ghazal; Najib Al Idrissi; Ayoub Saeidi; Abdelhalem Mesfioui; Hassane Zouhal (Medicina)
Background and Objectives: The insertion/deletion (I/D) polymorphism in ACE, the gene encoding the angiotensin-converting enzyme (ACE), has been suggested as a genetic variation that can influence exercise performance and risk of injury in elite athletes. The I allele has been associated with enhanced endurance performance and with reduced inflammation, while the D allele has been associated with improved performance in strength and power activities. However, the role of this genetic variant in the incidence of non-contact injury is underexplored. This study investigated the possible association of ACE I/D genotypes with the risk of non-contact injury in elite Moroccan athletes. Materials and Methods: Forty-three elite male athletes (19 cyclists and 24 field hockey players) from the Moroccan national team participated voluntarily. Non-contact injuries were recorded for all athletes and classified according to the IOC consensus statement by the medical staff of the teams. ACE I/D polymorphism genotyping was performed by polymerase chain reaction (PCR) using genomic DNA from blood samples. Results: There were four cyclists (21.05%) and eight field hockey players (33.33%) with a non-contact injury during the season. The distribution of the ACE I/D genotypes was similar in the athletes with vs. without non-contact injury for cyclists (DD/ID/II 25.00/50.00/25.00% vs. 46.67/40.00/13.33% non-injured, respectively; X2 = 0.69, p = 0.70), field hockey players (DD/ID/II 50.00/50.00/0.00% vs. 50.00/43.75/6.25%; X2 = 0.54, p = 0.76) and for the whole group of athletes (DD/ID/II 41.67/50.00/8.33% vs. 48.39/41.94/9.68%; X2 = 0.22, p = 0.89). In the whole group of athletes, neither the dominant (DD + ID vs. II = OR: 1.17, 95% CI: 0.15–16.56, p = 0.89) nor the recessive (DD vs. ID + II = OR: 1.31, 95% CI: 1.31–4.89, p = 0.69) models showed an increased risk of non-contact injury. Conclusions: The distribution of the ACE I/D genotypes was similar in elite cycling and field hockey athletes with or without non-contact injury during the season. These results indicate that there is no significant association between the ACE I/D polymorphism and the susceptibility to non-contact injury in these athletes. Further research is warranted to validate these findings and to investigate their broader implications for advancing knowledge in sports injury prevention and optimizing athlete management strategies.